Alexander von Humboldt, the Spanish crown and Hispanic science - Puig-Samper, Miguel Ángel (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2025)
The article examines Alexander von Humboldt’s relationship with Hispanic science and his interaction with peninsular and Creole scientists. It highlights how Humboldt, despite criticisms and misunderstandings about his use of Hispanic scientific works, maintained a significant relationship with the Spanish crown and its scientists. The importance of the administrative and political support Humboldt received is mentioned, as well as his interaction with Spanish scientists. During his American journey, Humboldt and Bonpland also collaborated with local scientists and figures, enriching their research and contributing to their work. In summary, the article underscores the relevance of collaboration and knowledge exchange between Humboldt and the Hispanic scientific community and how this influenced his discoveries, the new image of America on the European continent, and the perception of Hispanic science in the global context.